2002
DOI: 10.1149/1.1504041
|View full text |Cite
|
Sign up to set email alerts
|

Energy Transfer Between Tb[sup 3+] Ions in Y[sub 4−x]Tb[sub x]Al[sub 2]O[sub 9] Phosphor

Abstract: A generally known energy transfer route in Tb 3ϩ activated phosphors is the 5 D 3 → 5 D 4 cross relaxation and the subsequent 5 D 4 → defect impurity quenching. However, this mechanism is not satisfactory to explain the overall feature of measured decay curves of the 5 D 3 → 7 F j transition in the wide range of Tb 3ϩ concentrations. We suggested a new energy transfer scheme, where the 5 D 3 or 4 emission is quenched by the second type of cross relaxations from 5 D 3 or 4 to upper levels such as 5d, charge tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In order to qualitatively describe the temperature-dependent energy-transfer processes that take place in the Tb 3+ -doped systems, rate equations describing the population of each energy state of Tb 3+ ions were analyzed. We considered the forms of the state equations presented in eqs 1–8 for levels n i , where i = 1, 2, 3, 4, 5, 6, 7, and 8 correspond to the terms 7 F 6 , 7 F 5 , 7 F 4 , 7 F 3 , 7 F 2 , 7 F 1 , 7 F 0 , and 5 D 4 , respectively . The proposed equations cover the generation of transitions matched to GSA ( 7 F 6 → 5 D 4 ) or ESA ( 7 F 5 → 5 D 4 ) induced with a laser of an appropriate excitation wavelength (485 and 543 nm, respectively; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In order to qualitatively describe the temperature-dependent energy-transfer processes that take place in the Tb 3+ -doped systems, rate equations describing the population of each energy state of Tb 3+ ions were analyzed. We considered the forms of the state equations presented in eqs 1–8 for levels n i , where i = 1, 2, 3, 4, 5, 6, 7, and 8 correspond to the terms 7 F 6 , 7 F 5 , 7 F 4 , 7 F 3 , 7 F 2 , 7 F 1 , 7 F 0 , and 5 D 4 , respectively . The proposed equations cover the generation of transitions matched to GSA ( 7 F 6 → 5 D 4 ) or ESA ( 7 F 5 → 5 D 4 ) induced with a laser of an appropriate excitation wavelength (485 and 543 nm, respectively; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Choi et al [29] and Sohn et al [34] have suggested a second type of quenching mechanism for 5 D 3 and 5 D 4 excited levels based on the excited state absorption by a cooperative energy transfer from 5 D 3 or 5 D 4 levels to the upper laying levels (UL). According to them, this process has been proposed as in three possible ways such as (i) 5 D 4 -7 F 6 ) 5 D 4 -UL;…”
Section: Excitation and Fluorescence Spectramentioning
confidence: 99%
“…Upon 262 nm excitation, the emission spectra consist of blue sets at about 420 nm and some peaks from 480 to 650 nm. The blue band originates from 5 D 3 → 7 F 5 transition and the peaks are due to 5 D 4 → 7 F J ( J =6, 5, 4, 3) transitions of Tb 3+ , as shown in Figure B . From the inset, the quenching concentration of 5 D 3 and 5 D 4 is different.…”
Section: Resultsmentioning
confidence: 89%
“…7 F J (J=6, 5, 4, 3) transitions of Tb 3+ , as shown in Figure 7B. 28 From the inset, the quenching concentration of 5 D 3 and 5 D 4 is different. At low concentration, it mainly emits blue light from the 5 D 3 excited level.…”
Section: Luminescence Properties Of Tb 3+ Doped Materialsmentioning
confidence: 86%